Hypertension/prehypertension and its determinants in pediatric IgA nephropathy - Fu, Qing-Ying (Medicine (Baltimore), 2020)
Immunoglobulin A nephropathy (IgAN) is a major cause of secondary hypertension (HT) of renal origin – a significant prognostic factor of IgAN. In children, similar to HT, prehypertension (pre-HT) is becoming a significant health issue. However, the role of secondary HT and pre-HT (HT/pre-HT) in the progression of pediatric IgAN remains unclear. We investigated the effects of HT/pre-HT on prognosis and its determinants as well as their correlation with clinicopathological parameters to identify more effective therapeutic targets. This single-center retrospective study compared clinicopathological features and treatment outcomes between patients with and without HT/pre-HT in 108 children with IgAN. Independent risk factors for HT/pre-HT were evaluated; segmental glomerulosclerosis was a significant variable, whose relationship with clinicopathological parameters was analyzed. Clinical outcomes of patients with and without HT/pre-HT differed considerably (P = .006) on ≥6 months follow-up. Patients with HT/pre-HT reached complete remission less frequently than those without HT/pre-HT (P = .014). Age, serum creatinine, prothrombin time, and segmental glomerulosclerosis or adhesion were independent risk factors for HT/pre-HT in pediatric IgAN (P = .012, P = .017, P = .002, and P = .016, respectively). Segmental glomerulosclerosis or adhesion was most closely associated with glomerular crescents (r = 0.456, P < .01), followed by Lees grades (r = 0.454, P < .01), renal arteriolar wall thickening (r = 0.337, P < .01), and endocapillary hypercellularity (r = 0.306, P = .001). The intensity of IgA deposits, an important marker of pathogenetic activity in IgAN, was significantly associated with the intensity and location of fibrinogen deposits (intensity: r = 0.291, P = .002; location: r = 0.275, P = .004). HT/pre-HT in pediatric IgAN patients is an important modifiable factor. A relationship is observed between HT/pre-HT and its determinants, especially segmental glomerulosclerosis. Potential therapeutic approaches for IgAN with HT/pre-HT might be directed toward the management of coagulation status, active lesions, and hemodynamics for slowing disease progression.